2020
DOI: 10.1016/j.jsams.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of head impact exposure in men’s and women’s collegiate club water polo

Abstract: Objectives: Recent reports have demonstrated a risk of concussion and subconcussive head impacts in collegiate varsity and international elite water polo. We sought to characterize patterns of head impact exposure at the collegiate club level of water polo.Design: Prospective cohort study.Method: Head impact sensors (SIM-G, Triax Technologies) were worn by men's (n=16) and women's (n=15) collegiate club water polo players during 11 games. Peak linear acceleration (PLA) and peak rotational acceleration (PRA) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Most of the impacts we observed had a peak linear acceleration component < 32 g and a peak rotational acceleration component < 4 krads/s 2 , making them comparable to impacts measured in soccer and lacrosse with the same sensor used in the current study 56 , 57 . Note that the poor false-positive rate of the SIM-G in this study (92.4%) is well documented in water polo 45 , 46 , and is consistent with limitations of similar head impact sensors in land-based sports 58 , underscoring the importance of video review for interpretation of data collected with these sensors 59 . Likewise, it is quite unlikely that the sensors have a significant false-negative rate and, when considered together with the high interrater reliability between independent observers, it is also unlikely that exposure, as measured by the frequency of head impacts, is underestimated in our sample.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Most of the impacts we observed had a peak linear acceleration component < 32 g and a peak rotational acceleration component < 4 krads/s 2 , making them comparable to impacts measured in soccer and lacrosse with the same sensor used in the current study 56 , 57 . Note that the poor false-positive rate of the SIM-G in this study (92.4%) is well documented in water polo 45 , 46 , and is consistent with limitations of similar head impact sensors in land-based sports 58 , underscoring the importance of video review for interpretation of data collected with these sensors 59 . Likewise, it is quite unlikely that the sensors have a significant false-negative rate and, when considered together with the high interrater reliability between independent observers, it is also unlikely that exposure, as measured by the frequency of head impacts, is underestimated in our sample.…”
Section: Discussionsupporting
confidence: 85%
“…Our group previously demonstrated that exposure differed between males and females competing at the club level 46 , but the potentially interactive effect of competition level is unknown in water polo. Thus, we characterized head impact exposure for each team and tested for differences between teams based on sex and level of competition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings highlight the critical need for concussion-reduction strategies, which may benefit from different approaches for men and women; whereas the highest percentage of male concussions occurred via contact with another player, the highest percentage of female concussions occurred via contact with a playing device (ie, the ball). As several studies have shown position-specific differences in head impacts/concussions during play, 2 4 concussion-prevention strategies would be enhanced by more detailed injury surveillance data that include player-position information and a more thorough description of the injury mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The SIM-G telemetry system was utilized for this study because it can wirelessly record, store, and transmit real-time head impact data from nonhelmeted players and has been widely used in various sports examining head impact biomechanics. 6,14,16,33…”
Section: Head Impact Telemetrymentioning
confidence: 99%